Analysis of Factors That Influence Good Corporate Governance on Earnings Management in Manufacturing Company Listed in Indonesia Stock Exchange - Elok Dwi Vidiyastutik; Joni Hendra (Universitas Pendidikan Ganesha, 2020)
The consistent implementation of good corporate governance based on fairness, transparency, and accountability is proven to improve the quality of financial statements.This study aims to determine the influence of indicators of good corporate governance indicators to earnings management in Manufacturing Companies listed in Indonesia Stock Exchange (IDX). The sampling method is porposive samling by taking a sample of 30 manufacturing companies in the consumer goods industry sector which publishes annual report complete year 2014-2018.The results showed that simultaneously and partially, managerial ownership, composition of board of commissioner, audit committee and audit quality of KAP size have a positive effect on earnings management.Variable composition of board of commissioner has the most dominant influence to earnings management, shown by value of Standardized efficients Beta 0,303 bigger of the value of Standardized Coefficients Beta of other independent variables.